The Family History of Ṣilli-Ištar. A Reconstruction based on the Kutalla Documents - Ward, Richard David (2012)
A Thesis Submitted to the Faculty of the Graduate School of the University of Minnesota in Partial Fulfilment of the Requirements for the Degree of Doctor of Philosophy.